The impact of estrogen on periodontal tissue integrity and inflammation—a mini review - Palanisamy, Sucharitha (Frontiers in Dental Medicine, 2025)
Estrogen is said to be a crucial player in different aspects of periodontal health and disease, influencing a spectrum of cellular and molecular processes within periodontal tissues. Its receptors, ERα and ERβ, are expressed in various periodontal cells, suggesting direct responsiveness to hormonal fluctuations. Mechanistically, estrogen regulates osteoblast and osteoclast activity, thereby affecting bone turnover and maintenance of alveolar bone density. Studies indicate that estrogen upregulates the periodontal ligament stem cells' osteogenic differentiation (PDLSCs), promoting collagen synthesis and matrix mineralization critical for periodontal tissue integrity. Moreover, estrogen's anti-inflammatory properties modulate cytokine expression and immune responses in the periodontium, potentially attenuating periodontal inflammation and tissue destruction. Conversely, estrogen deficiency, such as in postmenopausal women, correlates with increased susceptibility to periodontal diseases characterized by greater clinical attachment loss and alveolar bone resorption. Hormone replacement therapy (HRT) with estrogen has shown promise in clinical settings, demonstrating beneficial effects on periodontal health by reducing inflammation and maintaining alveolar bone density. However, the adequacy and assurance of long-term estrogen supplementation in periodontal management require further investigation due to its systemic effects on other tissues and organs. Understanding the intricate interactions between estrogen and periodontal tissues is crucial for developing targeted therapies that leverage hormonal pathways to enhance periodontal health and mitigate disease progression effectively.